EFFECTIVENESS OF RED BITES FRUIT (Beta vulgaris) AS A MOUTH MOUTH TO REDUCE HALITOSIS: EFEKTIFITAS SARI PERASAN BUAH BIT MERAH (Beta Vulgaris) SEBAGAI OBAT KUMUR TERHADAP PENURUNAN TINGKAT HALITOSIS - I Gusti Ngurah Putra Dermawan; Intan Kemala Dewi; Fritz Gerald Dhrma Tedjamartono (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Halitosis or bad breath is often a problem because it can reduce the fluency of communication which causes embarrassment in socializing so that it has a psychological impact which results in low self-esteem, loss of self-image and can cause stress. This writing aims to determine the role of beets on the level of halitosis reduction. Review: Most of the known causes of halitosis come from food scrap left in the oral cavity which is processed by the normal flora of the oral cavity, and are the result of the production of the activity of bacteria in the mouth that causes the formation of Volatile Sulfur Compounds (VSC) in the oral cavity, which is a sulfur compound that is volatile and smells bad. Since time immemorial, many people believe that natural ingredients are able to treat various diseases because they are considered less likely to cause side effects compared to synthetic drugs. One of the natural ingredients that can be used is beetroot. Beetroot contains several active compounds such as carotenoids, saponins, glycine betanin, betanin, polyphenols, flavonoids, phenols, tannins and alkaloids. Beetroot is thought to be able to reduce the level of halitosis because the compounds in beets contain antibacterial active substances that can reduce bacteria in the oral cavity in reducing the level of halitosis. Conclusion: Beets (Beta Vulgaris) are effective in reducing the level of halitosis because they have antibacterial properties.